Cestovna rasvjeta kao element sigurnosti prometa - Širola, Eduard (Promet - Traffic&Transportation, 2012)
Exceptionally high incidence of road traffic accidents with casualties and fatalities as related to the actual traffic volumes occur during the night. However only some 25% of traffic (viewed on the average) happens in the night - time period. The paper deals with an analysis of a variety of available data on traffic accidents and their consequences (with particular reference to the metropolitan area of Zagreb) which serve the author to draw uncountable evidence that the hazards of nighttime driving surpass (excell) the hazards of daytime driving. Furthermore nighttime road traffic accidents are by their consequences of more severe nature than the daytime, while high-quality road lighting substantially reduces both the incidence of accidents and their adverse consequences.